The impact of liberal arts education on Egyptian student identity and worldview: a study of the core curriculum of the American University in Cairo - Guindi, Rami Wasfi Maurice (AUC Knowledge Fountain, 2019)
Liberal Arts Education advocates an enquiry about life at its very fundamental level. In contrast to other forms of higher education, it decidedly delves into the complicated task of engaging with student ontological, epistemological, and axiological foundations. Its mandate - and its promise - is to educate the formation of student identities and worldviews. For Egypt and the Middle East, where the study of humanities is in deep crisis, Liberal Arts Education programs present valuable initiatives to challenge the stagnant status quo and offer to students zones of freedom of thought and expression. It thus becomes imperative to ask: to what extent and in which forms do these programs really impact student identities and worldviews? As such, this thesis investigates the impact of the core curriculum of the American University in Cairo, as a Liberal Arts Education model, on two essential constructs: student identity and student worldview. The central research question is: how does the core curriculum of AUC impact student identity and worldview? In its attempt to answer this question, the research treats the core curriculum, not as rigid content, but as a dynamic platform across which administrators, faculty and students interact. The research employs four data collection techniques: document analysis, faculty interviews, student survey and student focus groups. While the documents and the faculty interviews shed lights on the historical, structural, and implementation aspects of the core curriculum, the student survey and focus groups reveal student perceptions of the program and of its impact on their identities and worldviews. Whereas the research affirmed overall institutional commitment to the values of liberal arts education as well as student belief in its potential, it exposed a gap between the theoretical potential of the program and its actual impact on students. According to the students, faculty readiness is an essential factor to account for this gap. The research opens the door for further questions about what is needed for the program to fulfill its full potential. Also, an identity and worldview instrument is worth producing.